Effect of Scanning Origin Location on Data Accuracy of Abutment Teeth Region in Digital Impression Acquired Using Intraoral Scanner for Removable Partial Denture: A Preliminary In Vitro Study - Kim Eung-Yeol; Wada Junichiro; Sakamoto Kazuki; Ishioka Yurika; Arai Yuki; Murakami Natsuko; Yamazaki Tshiki; Hayama Hinonari; Utsumi Miona; Inukai Shusuke; Wakabayashi Noriyuki (MDPI, 2025)
The aim of this study was to investigate the effect of scanning origin location on the data accuracy of removable partial denture (RPD) abutment teeth region in digital impressions acquired by an intraoral scanner. A mandibular partially edentulous model including the following target abutment teeth was used: the left second molar (#37); left first premolar (#34); and right second premolar (#45). The following scanning strategies were tested: the strategy starting from #37 to mesial direction (37M); strategies starting from #34 to mesial (34M) and distal directions (34D), and strategies starting from #45 to mesial (45M) and distal directions (45D). The evaluated measures were trueness, precision, and linear accuracy. One-way and two-way ANOVA were performed for the comparison of trueness and linear accuracy, while Kruskal-Wallis test was performed for the precision comparison (alpha = 0.05). 45M and 45D showed significantly superior trueness of #34 to 37M and 34D. 45M also showed significantly superior trueness of #45 to 34. 45D showed significantly inferior linear accuracy of #34 and superior linear accuracy of #45 compared to other strategies. It was concluded that scanning origin location would have an impact on data accuracy of RPD abutment teeth region in digital impressions acquired by intraoral scanner.